Implementation Strategy Learning Based Project -Based Learning For Increase Ability Think Critical Elementary school students - Yeni Nuraeni; Zulfa Muthia Bilqis; Shilla Safitri; Muhammad Rohim (Jurnal Pengetahuan dan Pendidikan, 2025)
This study aims to examine the application of Project Based Learning (PjBL) strategies in improving the critical thinking skills of elementary school students. PjBL is a learning model that is oriented towards real-life activities and is student-centered, where students are actively involved in completing projects that require them to use analytical, evaluation, and problem-solving skills—the main components of critical thinking. This model not only emphasizes mastery of concepts, but also the development of higher-order thinking skills through collaborative and exploratory activities that are relevant to students' real-world situations. Data analysis involved comparing critical thinking test scores before and after learning using PjBL as well as qualitative descriptions of changes in student attitudes and engagement. The results showed that the implementation of the PjBL strategy significantly improved students' critical thinking skills. Students became more active in asking questions, discussing, and solving problems independently and collaboratively during the project work. In addition to improving critical thinking test scores, students were also able to apply learning concepts in real contexts through project products such as life cycle models or ecosystem maps, which served as concrete evidence of their understanding and critical thinking skills. In addition, the project-based learning process fostered students' learning motivation and self-confidence. Project-Based Learning (PjBL) also helps teachers manage learning that focuses on 21st-century skills, such as collaboration, creativity, and decision-making. Challenges, such as time management and varying student abilities, can be addressed with careful planning and teacher guidance throughout the project cycle. Overall, the Project-Based Learning strategy is effective as a learning approach in elementary schools to develop students' critical thinking skills while enriching learning experiences that are meaningful and applicable to everyday life